Pentingnya Kesadaran akan Perlindungan Data Pribadi dan Etika Bermedia Sosial - Sudarawerti, Galuh; Fariz, Fariz; Kharisma, Mita (Transpublika Publisher, 2025)
The team from Telkom University carried out community service activities at the Al Falah At Tirmidzi Foundation with the aim of increasing digital literacy and awareness of students, teachers, and foundation managers regarding personal data protection and social media ethics. This program began with coordination and assessment regarding the relevance of the material to be provided with the needs of the target community, then continued with the delivery of educational materials, interactive discussions, pre-tests and post-tests, and satisfaction surveys regarding the implementation of the activity. The results of the activity showed a significant increase in participants' understanding of the differences between general and specific personal data, as well as the importance of responsible behavior on social media. This activity not only builds awareness of the legal and ethical dimensions of digital behavior, but also encourages the creation of a safer and more empathetic digital space. This program received a positive response and was considered relevant and had an impact on the target community.